Stone cold lover - Warren, Christine (St. Martin's Paperbacks, 2014)
Art restorer Felicity "Fil" Shaltis can read the magic in auras, but her fascination with a valuable statue her friend Ella Harrow asks her to locate is purely artistic. At least until the fierce stone gargoyle comes to life as a powerful, and powerfully hot, immortal warrior, who promptly saves her life from a cultist set on destroying them both. Suddenly "chiseled good looks" takes on a whole new meaning...